In vitro efficacy of fungicides and plant extracts on the growth of Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. and Sclerotium rolfsii Sacc. the causal organisms of anthracnose and soft rot of jute - Hosen, Sarowar; Shamsi, Shamim; Bashar, MA (Dhaka University Journal of Biological Sciences, 2016)
Abstract not available Dhaka Univ. J. Biol. Sci. 25(2): 195-199, 2016 (July)